Paradigmatics in system lexical relations in modern Russian language (on the basis of synonyms’ research) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article deals with paradigmatics in system lexical relations in modern Russian language. System relations are most notably explored on vocabulary level. The correlations among linguistic units which are based on common component are expressed in synonyms. The dictionaries of synonyms reflect the functioning and development of lexical system in modern Russian language. Synonyms are different in their shades of meaning, stylistic nuances, and perform a set of functions in language.
Keywords: paradigm; synonymy; lexicography; system relations; compatibility